(3ZQQ GdNUGFU GdhGVMI hZQQ GdfbGFU GdaGVMIs - (3GdCfUGQj GdcJHj, GdhWhGW (B- (3LeGd GdOjf, eMeO Hf EHQGgje Hf jMji Hf Ydj, J (B718 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GddSGf YfhGf Ybd GdEfSGf (B... (3aEfj deG QCjJ JZGjQ eYGfj GdCNdGb OGdG Ydi JHGjf eHGfj GdCYQGb hGdfahS JJaGhJ aj ejdgG Edi CZQGVgG Ydi MSH GNJdGa LhGgQgG (B...s
(3BNQgG (B:s
(3GdaUd GdKGdK YTQ ef GdHGH GdSGOT YTQ ajeG jNJe Hg gPG GdcJGH ef OYGA fQLh ef Gddg Cf ojSeY hjLGH bGd Gddg JYGdi (B{ (3bd eG jYHC Hce QHj dhdG OYGDce (B} ... (3hUdi Gddg Ydi SjOfG eMeO hBdg hSdes
(3JHUQI GdYfhGf (B:s
(3hbO ZdW GdRQcdj hUfag aj GdcjejGA hGdWHjYI hGdUhGH Cfg aj GdCNdGb hGdeMGeO , hdcfg bGd gh aj SJI eLdOGJ adYd gPG HYVgGs
(3JHUQI GdeDda (B:s
(3Ydi WQI GdeNWhW Hbde eZGjQ (B: " (3hQCjJ fSNI TGejI ef gPG GdcJGH efShHI Edi GdTjN LeGd GdOjf CHj YHO Gddg GHf GdTjN EHQGgje Hf YeQ GdhQOj GdeYQha HGdhWhGW QMeg Gddg (B" (3hde CLOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\297s
Keywords: (3GdJUha hGdBOGH GdTQYjIs